Respuesta :

-f + 4f + 2 = 8 - 3f

3f + 2 = 8 - 3f

6f = 6

f = 1

−f+2+4f=8−3f

Add −f

and 4f

.

3f+2=8−3f

Move all terms containing f

to the left side of the equation.

Add −3f

to both sides of the equation.

3f+2+3f=8

Add 3f

and 3f

6f+2=8

Move all terms not containing f

to the right side of the equation.

Subtract 2

from both sides of the equation.

6f=−2+8

Add −2

and 8

6f=6

Divide each term by 6

and simplify.

Divide each term in 6f=6

by 6

6f6=66

Reduce the expression by cancelling the common factors.

f=66

Divide 6

by 6

f=1